Ischemic Stroke in Non-Gender-Related CHA2DS2-VA Score 0~1 Is Associated With H2FPEF Score Among the Patients With Atrial Fibrillation - Kim, Min; Yu, Hee Tae; Kim, Tae-Hoon; Lee, Dae-In; Uhm, Jae-Sun; Kim, Young Dae; Nam, Hyo Suk; Joung, Boyoung; Lee, Moon-Hyoung; Heo, Ji Hoe; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Background: Ischemic strokes (ISs) can appear even in non-gender-related CHA2DS2-VA scores 0~1 atrial fibrillation (AF) patients. We explored the determinants associated with IS development among the patients with non-gender-related CHA2DS2-VA score 0~1 AF. Methods and Results: In this single-center retrospective registry data for AF catheter ablation (AFCA), we included 1,353 AF patients (24.7% female, median age 56 years, paroxysmal AF 72.6%) who had non-gender-related CHA2DS2-VA score 0~1, normal left ventricular (LV) systolic function, and available H2FPEF score. Among those patients, 113 experienced IS despite a non-gender-related CHA2DS2-VA score of 0~1. All included patients underwent AFCA, and we evaluated the associated factors with IS in non-gender-related CHA2DS2-VA score 0~1 AF. Patients with ISs in this study had a lower eGFR (p<0.001) and LV ejection fraction (LVEF; p=0.017), larger LA diameter (p<0.001), reduced LA appendage peak velocity (p<0.001), and a higher baseline H2FPEF score (p=0.018) relative to those without ISs. Age (OR 1.11 [1.07-1.17], p<0.001, Model 1) and H2FPEF score as continuous (OR 1.31 [1.03-1.67], p=0.028, Model 2) variable were independently associated with ISs by multivariate analysis. The eGFR was also independently associated with IS at low CHA2DS2-VA scores in both of Models 1 and 2. AF recurrence was significantly higher in patients with IS (Log-rank p<0.001) but did not those with high H2FPEF scores (Log-rank p=0.079), respectively. Conclusions: Among the patients with normal LVEF and non-gender-related CHA2DS2-VA score 0~1 AF, the high H2FPEF score, and increasing age were independently associated with IS development. (ClinicalTrials.gov Identifier: NCT02138695)